2003
DOI: 10.1002/bit.10748
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nickel and chromium nanoparticles using the protein cage of apoferritin

Abstract: The iron storage protein, apoferritin, has a cavity in which iron is oxidized and stored as a hydrated oxide core. The size of the core is about 7 nm in diameter and is regulated by the cavity size. The cavity can be utilized as a nanoreactor to grow inorganic crystals. We incubated apoferritin in nickel or chromium salt solutions to fabricate hydroxide nanoparticles in the cavity. By using a solution containing dissolved carbon dioxide and by precisely controlling the pH, we succeeded in fabricating nickel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 11 publications
(15 reference statements)
0
154
0
Order By: Relevance
“…A synthesis of ferrimagnetic ferritin (γ-Fe 2 O 3 ) was achieved by a chemical remineralization procedure [7,8] with the assistance of H 2 O 2 oxidant in 3-[(1,1-dimethyl-2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid(AMPSO) buffer (pH 8.5) at 65 o C under N 2 gas. Biomineralization of other metals (i.e., Co [9,11], Mn [12][13][14], Ni [15], and Pd [16]), semiconductors (CdS) [17], and metal-oxo-anions composites [18] into the ferritin cavity has also been reported. Wong et al demonstrated the magnetic transition from superparamagnetic to ferromagnetic CoPt cored ferritin [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A synthesis of ferrimagnetic ferritin (γ-Fe 2 O 3 ) was achieved by a chemical remineralization procedure [7,8] with the assistance of H 2 O 2 oxidant in 3-[(1,1-dimethyl-2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid(AMPSO) buffer (pH 8.5) at 65 o C under N 2 gas. Biomineralization of other metals (i.e., Co [9,11], Mn [12][13][14], Ni [15], and Pd [16]), semiconductors (CdS) [17], and metal-oxo-anions composites [18] into the ferritin cavity has also been reported. Wong et al demonstrated the magnetic transition from superparamagnetic to ferromagnetic CoPt cored ferritin [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Arrays of inorganic particles can be created from self-assembled structures of biomaterials. For example, Yamashita and coworkers demonstrated use of a biomolecular array for structure transcription (figure 68) [617,618]. Ferritin, which is composed of 24 self-assembled peptide subunits and capable of including iron oxide, was assembled as a Langmuir monolayer then transferred onto a hydrophobized silicon substrate forming a two-dimensional hexagonal array of ferritin.…”
Section: Inorganic Substancesmentioning
confidence: 99%
“…These properties can be achieved not only by using the nanoreactor route but also by using apoferritin shell reassembly in the presence of target NPs [63]. [53,65,[70][71][72][73]. The scheme of NP synthesis using apoferritin is presented in Figure 3.…”
Section: Synthesis Of Nanoparticles Within the Apoferritin Cagementioning
confidence: 99%